Myofibroblastoma of the Breast: A Morphologic and Immunohistochemical Study of Three Cases - Hiva Saffar; Dorna Motevalli; Nasibeh Seirfar; Mahsa Ebrahimi; Perikala Vijayananda Kumar; Farid Kosari; Hedieh Moradi Tabriz; Sadaf Naderi; Golsa Shekarkhar (Iranian Society of Pathology, 2021)
Myofibroblastoma (MFB) of the breast is an uncommon entity of benign spindle neoplasms of the breast. This tumour possesses a broad spectrum of histomorphological patterns. Distinguishing of myofibroblastoma variants from malignant mimics of this benign neoplasm is essential for pathologists to avoid further invasive surgical procedures. In this article, we report the clinical, morphological, and immunohistochemical features of three cases, including two females and one male patient with mammary myofibroblastoma with emphasis on the histomorphological findings. As there is not yet enough information about MFB, more reports of MFB are still required to more clarify the pathogenesis and potential predisposing factors of this rare type of breast tumours.